Contemporary Asian living rooms - Jotisalikorn, Chami (Periplus, 2004)
Contemporary Asian Living Rooms takes you into 50 of Southeast Asia’s most inspiring homes and hotels. Dozens of beautiful interiors, displayed in more than 150 full-color photographs, provide the most up-to-date design ideas. Created by some of the leading talents in contemporary Asian design today, these interiors feature creative shapes, contours, materials, and new ways of working with the space where family and friends spend most of their time. An excellent volume for browsing, and a perfect source book for ideas.